The impact of healthcare delivery configuration on patients’ perceived service quality: The mediating role of patient trust and the moderating effect of secular rationality in Nanning - Haohai, Wang; Rehman, Asad Ur; Nawal, Ayesha; Khan, Waris Ali; Ullah, Ihtisham (Edelweiss Applied Science and Technology, 2026)
This study investigates how Healthcare Delivery Configuration (HDC) impacts Patients' Perceived Service Quality (SQ) in smart healthcare environments, specifically examining the mediating role of Patient Trust (PT) and the moderating influence of Secular Rationality (SR). A cross-sectional survey yielded 465 valid responses from tertiary hospital patients in Nanning, China. Data were analyzed using SPSS and AMOS, employing Confirmatory Factor Analysis (CFA) for validation and Structural Equation Modeling (SEM) with bootstrap sampling to test mediating and moderating effects. Results indicate that HDC significantly and positively predicts SQ. Patient Trust serves as a partial mediator, explaining approximately 20% of the total effect. However, the moderating effect of Secular Rationality was not statistically significant, suggesting that institutional efficiency builds trust across diverse individual value orientations. The study confirms a synergy between "hard" technical configuration and "soft" psychological trust. In high-stakes public healthcare, robust institutional design possesses a universal capacity for trust-building that transcends individual rational orientations. Hospital administrators should prioritize optimizing intelligent resource scheduling and transparency. Since individual rationality did not significantly moderate outcomes, implementing standardized, equalized smart healthcare strategies is essential for enhancing regional service quality.